Türkiye – Avrupa Topluluğu Ortaklık İlişkisinin Hukuki Çerçevesi - Hacı Can (Ankara Avrupa Çalışmaları Dergisi)
This study analyzes the legal framework of the association relationship between the European Community and Turkey, which was conceived originally as preparatory phase to a future membership of Turkey in the European Economic Community at that time. It discusses within this fra ınework among other things the questions over the material areas as well as the institutional structure of the association